Attitudes Toward Asylum Seekers: Evidence from Germany - Anselm Hager; Susanne Veit (Public Opinion Quarterly, 2019)
What theories explain variation in public opinion toward asylum seekers? We implement a survey experiment in which a representative sample of German residents evaluates vignettes of asylum seekers, which randomly vary attributes that speak to deservingness, economic and religious threat, and gender considerations of attitude formation. We find strong support for deservingness theories. Economic and religious threat theories also receive empirical support. Gender plays a negligible role. Importantly, we also document that economic and—to a lesser extent—religious threat considerations only matter when respondents evaluate economic refugees. By contrast, political refugees are welcomed nearly unconditionally. Our paper thus replicates key findings from Bansak, Hainmueller, and Hangartner (2016) and Czymara and Schmidt-Catran (2016) using a representative sample and points to an important interaction effect in public opinion formation toward asylum seekers: economic threat only gets activated when refugees' deservingness is in doubt.
Keywords: 330